Publikasi Karya Arsitektur Sebagai Strategi Pemasaran Bagi Konsultan Arsitektur - Dewi Ratih Purnamasari; I Komang Gelda Manika Aprizio; Komang Junida Aryadi Putra; I Wayan Widanan; Cokorda Istri Arina Cipta Utari (Undagi : Jurnal Ilmiah Jurusan Arsitektur Universitas Warmadewa, 2021)
Architectural consultants are very dependent on the presence of service users or clients, one of the marketing strategies that is usually used without violating the Indonesian Architectural Association's code of ethics is the publication of works that have been produced. Publication of this work can use various media, such as print media (books/magazines), Social Media (Instagram, Facebook, Web), Exhibitions, Online Media, and can also be in the form of architecture students or community activities. With the advancement of technology, architectural consultants can eliminate limitations in publishing their works for marketing. By applying the Marketing Funnel theory, it explains how to reach the market and get new market segments. Several phases will be obtained by the client, namely the Awareness Phase which can increase new audiences, the Preference Phase, which is when you can convince the client with the service products provided, this it is hoped that the client can reach the Loyalty Phase when the client has continuity in working with the Consultant. Architecture.